2017
DOI: 10.3390/molecules23010081
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of New Substituted Diquinolinyl-Pyridine Ligands as Anticancer Agents by Targeting G-Quadruplex

Abstract: G-quadruplexes (G4) are stacked non-canonical nucleic acid structures found in specific G-rich DNA or RNA sequences in the human genome. G4 structures are liable for various biological functions; transcription, translation, cell aging as well as diseases such as cancer. These structures are therefore considered as important targets for the development of anticancer agents. Small organic heterocyclic molecules are well known to target and stabilize G4 structures. In this article, we have designed and synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In contrast, other novel ligands were reported to be selective compounds interacting not only with a unique G4, but also with a narrow-spectrum of G4s. Among them, new substituted diquinolinyl-pyridine ligands show a preference for the parallel conformation of telomeric, c-MYC and c-KIT G4s [59]. The same selectivity pattern was confirmed for APTO-253, a phenanthroline derivative that is in phase I clinical trials for the treatment of acute myeloid leukemia [41].…”
Section: Selective G4 Ligandsmentioning
confidence: 66%
“…In contrast, other novel ligands were reported to be selective compounds interacting not only with a unique G4, but also with a narrow-spectrum of G4s. Among them, new substituted diquinolinyl-pyridine ligands show a preference for the parallel conformation of telomeric, c-MYC and c-KIT G4s [59]. The same selectivity pattern was confirmed for APTO-253, a phenanthroline derivative that is in phase I clinical trials for the treatment of acute myeloid leukemia [41].…”
Section: Selective G4 Ligandsmentioning
confidence: 66%
“…The interactions of azacyanines with tel24 were first investigated using UV-Vis and circular dichroism (CD) spectroscopy in order to quickly survey and confirm the presence of interactions between the azacyanines and tel24. Such a survey also reveals changes in the secondary structure of tel24 upon azacyanine binding and the effect of azacyanine structure on tel24 binding [25,[28][29][30][31][32][33][34][35][36][37]. Our previous structural studies using NMR have shown that one azamethyl was binding to one tel24 G-quadruplex structure between the top quartet and the A-T base pairing in the loop region.…”
Section: Determination Of Binding Using Uv-vis and CD Spectroscopymentioning
confidence: 92%
“…All samples were prepared in 25 mM potassium phosphate buffer (pH 7.0) and 70 mM KCl, unless otherwise stated. Samples were annealed by heating to 95 • C for 5 min in a water bath and then cooling overnight to room temperature prior to each experiment (19,25,33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the pyridine derivatives are quite essential compounds with the incredible biological applications (25,26). The new compounds, which contain a trimeric phosphazene ring with 2-pyridyl pendant arm, may be considered to have possibly antimicrobial, anticancer, antituberculosis, and antiproliferative activities.…”
Section: Introductionmentioning
confidence: 99%